Globalization and The Cultural Politics of Tradition Some Lessons from Developing Countries - Fadjar I. Thufail (LIPI Press, 1997)
Globalization in this time is popular discourse specially in economic actors. Though, development of globalization theory just has taken its first step. Both in popular discourse and economic theory relate with economic aspect and social globalization inter-nation. Then, for this time rarely to see the relation between globalization and cultural-political process in local level. This article try to offer another approach for analysing of globalization process that focus on social and cultural context in development country. In this type of analysing, research for â€œvernacularizationâ€ process like forms of global culture is very important as global community forming process. The relation for this article, anthropology offer an critical view to analyze global process that happen in daily life in the world.